The self-assembly of redox active peptides: Synthesis and electrochemical capacitive behavior - Piccoli, Julia P. [UNESP]; Santos, Adriano [UNESP]; Santos-Filho, Norival A. [UNESP]; Lorenzón, Esteban N. [UNESP]; Cilli, Eduardo M. [UNESP]; Bueno, Paulo R. [UNESP] (Wiley, 2016)
The present work reports on the synthesis of a redox-tagged peptide with self-assembling capability aiming applications in electrochemically active capacitive surfaces (associated with the presence of the redox centers) generally useful in electroanalytical applications. Peptide containing ferrocene (fc) molecular (redox) group (Ac-Cys-Ile-Ile-Lys(fc)-Ile-Ile-COOH) was thus synthesized by solid phase peptide synthesis (SPPS). To obtain the electrochemically active capacitive interface, the side chain of the cysteine was covalently bound to the gold electrode (sulfur group) and the side chain of Lys was used to attach the ferrocene in the peptide chain. After obtaining the purified redox-tagged peptide, the self-assembly and redox capability was characterized by cyclic voltammetry (CV) and electrochemical impedance-based capacitance spectroscopy techniques. The obtained results confirmed that the redox-tagged peptide was successfully attached by forming an electroactive self-assembled monolayer onto gold electrode. The design of redox active self-assembly ferrocene-tagged peptide is predictably useful in the development of biosensor devices precisely to detect, in a label-free platform, those biomarkers of clinical relevance. © 2016 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 357–367, 2016.
Keywords: electroactive peptide; electrochemical characterization; redox peptide monolayers; redox probe peptide; self-assembly